Incidence and Outcome of Acute Myocardial Infarction in Patients With Aortic Dissection and Risk Factor Control - Liu, Fang; Qian, Si-Chong; Jing, Shuai; Wang, Zhe; Yang, Xin-Chun; Chen, Mu-Lei (Frontiers in Surgery, 2021)
Background and aims: The contradiction of management modality between acute myocardial infarction(AMI) and aortic dissection(AD) may result in clinical catastrophe. Data on risk factors, incidence and outcome of AD and AMI are limited, and there have been no studies on the long-term outcomes of AMI in patients with AD. So we aimed to investigate long-term outcomes after AMI in patients with AD, and propose a useful diagnostic paradigm. Methods: Consecutively enrolled patients with AD and AMI who were referred to our center from 2010 to 2017. Baseline patient characteristics, risk factors, all medical treatments, echocardiographic parameters, laboratory data and treatment were recorded. All patients were followed up from the first hospitalization until a first heart event, death or 17 March, 2018. Results: 0.13% in AMI and 7.49% in AD patients had a concomitant diagnosis of AD and AMI. The average patient age was 53.3±12.1 years and 84.6% were male. The most prevalent vascular risk factors were hypertension (69.2%) and current smoker (64.1%). Of all the 39 patients, 66.7% were managed surgically. Overall in-hospital mortality was 10.3%. The 30-day and 5-year fatality rates were 23.1% and 35.9%, but were higher for female than for male(66.7% vs 30.3%, log-rank P = 0.045) on 5-year mortality. The overall survival of females was inferior to the males (log-rank P =0.045). Conclusions: Patients with AMI and AD exhibit high 5-year fatality rates. For these patients, surgical management tend to have lower mortality. Improved management of hypertension and smoking, may reduce future incidence rates.